The Effect of Capital Structure, Cash Flow, Market Value Added, and Net Profit Margin on Stock Returns of Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2020–2022 Period - Angelia, Nia; Sembiring, Santy Chatarina; Syahputra, Oky (Fakultas Ekonomi Prodi Akuntansi, 2025)
Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) are companies engaged in the processing and distribution of food and beverage products, whose shares are traded on the Indonesian capital market. This study aims to determine the effect of Capital Structure, Cash Flow, Market Value Added, and Net Profit Margin on Stock Returns of food and beverage companies listed on the IDX for the period 2020–2022. The population of this study includes all food and beverage companies listed on the IDX during the 2020–2022 period, totaling 40 companies. The number of samples used in this study is 23 companies over a period of 3 years, resulting in a total of 69 research samples. The results of the study partially show that Debt to Equity Ratio has a negative and insignificant effect on Stock Returns, Operating Cash Flow has no significant effect on Stock Returns, Market Value Added has a positive and significant effect on Stock Returns, and Net Profit Margin has no significant effect on Stock Returns. Meanwhile, simultaneously, Debt to Equity Ratio, Operating Cash Flow, Market Value Added, and Net Profit Margin have a positive and significant effect on Stock Returns.